Natalia Osadcha-Yanata (1891–1982): Pages of Biography - Gamaliia, V. M. (History of science and technology, 2018)
The article is devoted to the study of the life and activities of the wife and friend of the prominent Ukrainian scientist-botanist Oleksandr Aloizovych Yanata – Natalia Osadcha-Yanata. The role of this woman in the development of Ukrainian science, culture and education was shown, as well as its contribution to the study of the problems of the development of the botanical nomenclature and the terminology of medicinal plants. Osadcha-Yanata’s scientific work began after graduating from the Faculty of Physics and Mathematics of the Kiyv higher women’s courses. The significance of Natalia’s acquaintance with her future husband O. A. Yanata on the formation of her scientific interests and further work in the fields of science is stressed. The data on the activity of a scientist in the commission on the preservation of monuments of nature and antiquity of the Crimean Society of amateurs and researchers of nature, it’s role in the implementation of the Ukrainian language into all spheres of public life is given. The importance of Natalia’s work as the secretary of the terminological commission of the botanical section of the Ukrainian Scientific Society, and then her role in the development of native terminology in academic institutions is emphasized. The periodization of N. Osadcha-Yanata’s scientific activity is proposed, the foreign stage of her work after leaving abroad is outlined. The contribution of N. Osadcha-Yanata to the creation of the manuscript of the dictionary of the botanical nomenclature, as well as the preparation of the fundamental works “Ukrainian Botanical Terminology” and “Ukrainian Botanical nomenclature” are shown. Unfortunately, these researches have not been published. The facts, which prove the devotion of N. Osadcha-Yanata to the scientific work, are presented. So, even after his husband was repressed in 1933, all his work was banned, and Natalia herself was dismissed from work, she continued studying the plant life of Ukraine. This activity Osadcha-Yanata also continued after her forced emigration (first to West Germany, and later to the United States). The article tells about the difficult life of Ukrainian emigrant scholars, as well as their devotion to science, which helped to continue research activities far from the Motherland. In particular, materials collected by N. Osadcha-Yanata in Ukraine were published almost 40 years later as a monograph entitled “Ukrainian Folk Names of Plants”. And many of her manuscripts are still stored in the Archives of Columbia University.